Hülle Cells of Aspergillus nidulans with Nuclear Storage and Developmental Backup Functions Are Reminiscent of Multipotent Stem Cells - Danielle M. Troppens (American Society for Microbiology, 2020)
ABSTRACT Some aspergilli are among the most cosmopolitan and ecologically dominant fungal species. One pillar of their success is their complex life cycle, which creates specialized cell types for versatile dispersal and regenesis. One of these cell types is unique to aspergilli—the Hülle cells. Despite being known for over a century, the biological and ecological roles of Hülle cells remain largely speculative. Previously reported data on in vivo Hülle cell formation and localization have been conflicting. Our quantification reveals that Hülle cells can occur at all locations on hyphae and that they show cellular activity similar to that seen with adjacent hyphae, indicating that they develop as intricate parts of hyphal tissue. In addition, we show that during sexual development associated with two parental strains, the typically multinucleate Hülle cells can inherit nuclei from both parents, indicating that they may serve as genetic backups. We provide an easy, reproducible method to study Hülle cell biology and germination with which we investigate the 90-year-old puzzle of whether and how Hülle cells germinate. We present clear evidence for the germination of Hülle cells, and we show that Hülle cells grow hyphae that develop into a spore-producing colony. Finally, we show that Hülle cell-derived colonies produce conidiospores faster than spore-derived colonies, providing evidence for an as-yet-undescribed developmental shortcut program in Aspergillus nidulans. We propose that Hülle cells represent a unique cell type as specialized hypha-derived sexual tissue with a nucleus storage function and may act as fungal backup stem cells under highly destructive conditions. IMPORTANCE The in vivo identification of Hülle cells in cases of aspergillosis infections in animals and humans illustrates their biological relevance and suggests that they might be involved in pathogenicity. It is striking that aspergilli have developed and maintained a multinucleate nurse cell that is presumably energy-intensive to produce and is usually found only in higher eukaryotes. Our findings shed light on how the understudied Hülle cells might contribute to the success of aspergilli by acting not only as nurse cells under detrimental conditions (sexual development) but also as fungal backup stem cells with the capacity to produce genetically diverse spores in an accelerated manner, thereby substantially contributing to survival in response to predator attack or under otherwise severely destructive conditions. Our study solved the 90-year-old puzzle of Hülle cell germination and provides easy, reproducible methods that will facilitate future studies on biological and ecological roles of Hülle cells in aspergilli.